American government and politics today - Schmidt, Steffen W.; Shelley, Mack C.; Bardes, Barbara A. (Wadsworth, 2014)
Experience the excitement that comes with being an active, engaged, and informed citizen. This latest edition includes a variety of updates including in-depth coverage of the 2012 elections and will help you understand the basic foundations of American government and why it all matters. - Back cover